Fuzzy-logic modeling of Fenton's oxidation of anaerobically pretreated poultry manure wastewater - Yetilmezsoy, Kaan (SPRINGER HEIDELBERG, 2012)
A multiple inputs and multiple outputs (MIMO) fuzzy-logic-based model was proposed to estimate color and chemical oxygen demand (COD) removal efficiencies in the post-treatment of anaerobically pretreated poultry manure wastewater effluent using Fenton's oxidation process. Three main input variables including initial pH, Fe+2, and H2O2 dosages were fuzzified in a new numerical modeling scheme by the use of an artificial intelligence-based approach. Trapezoidal membership functions with eight levels were conducted for the fuzzy subsets, and a Mamdani-type fuzzy inference system was used to implement a total of 70 rules in the IF-THEN format. The product (prod) and the center of gravity (centroid) methods were applied as the inference operator and defuzzification methods, respectively. Fuzzy-logic predicted results were compared with the outputs of two first-order polynomial regression models derived in the scope of this study. Estimated results were also compared to the multiple regression approach by means of various descriptive statistical indicators, such as root mean-squared error, index of agreement, fractional variance, proportion of systematic error, etc. Results of the statistical analysis clearly revealed that, compared to conventional regression models, the proposed MIMO fuzzy-logic model produced very smaller deviations and demonstrated a superior predictive performance on forecasting of color and COD removal efficiencies with satisfactory determination coefficients over 0.98. Due to high capability of the fuzzy-logic methodology in capturing the non-linear interactions, it was demonstrated that a complex dynamic system, such as Fenton's oxidation, could be easily modeled.
Keywords: Poultry manure wastewater; Anaerobic digestion; Fenton's oxidation; COD removal; Fuzzy-logic; Regression model; BIOMASS OEDOGONIUM SP; PERFORMANCE EVALUATION; AQUEOUS-SOLUTIONS; DISSOLVED-OXYGEN; NEURAL-NETWORKS; REMOVAL; PREDICTION; REACTOR; COD; DEGRADATION; Environmental Sciences & Ecology